If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (0.35)(s + 0.34) + (0.15s) = (0.2s + -1.66) Reorder the terms: 0.35(0.34 + s) + (0.15s) = (0.2s + -1.66) (0.34 * 0.35 + s * 0.35) + (0.15s) = (0.2s + -1.66) (0.119 + 0.35s) + (0.15s) = (0.2s + -1.66) Combine like terms: 0.35s + (0.15s) = 0.5s 0.119 + 0.5s = (0.2s + -1.66) Reorder the terms: 0.119 + 0.5s = (-1.66 + 0.2s) Remove parenthesis around (-1.66 + 0.2s) 0.119 + 0.5s = -1.66 + 0.2s Solving 0.119 + 0.5s = -1.66 + 0.2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-0.2s' to each side of the equation. 0.119 + 0.5s + -0.2s = -1.66 + 0.2s + -0.2s Combine like terms: 0.5s + -0.2s = 0.3s 0.119 + 0.3s = -1.66 + 0.2s + -0.2s Combine like terms: 0.2s + -0.2s = 0.0 0.119 + 0.3s = -1.66 + 0.0 0.119 + 0.3s = -1.66 Add '-0.119' to each side of the equation. 0.119 + -0.119 + 0.3s = -1.66 + -0.119 Combine like terms: 0.119 + -0.119 = 0.000 0.000 + 0.3s = -1.66 + -0.119 0.3s = -1.66 + -0.119 Combine like terms: -1.66 + -0.119 = -1.779 0.3s = -1.779 Divide each side by '0.3'. s = -5.93 Simplifying s = -5.93
| 9(b+1)=3b+15 | | 3g+2(-7+3g)=1-g | | (3x+5y)-(4x+11)=0 | | 17y-5x=46 | | .14(14+3.5)-3q=9 | | -5=r-13 | | 2y+3=3(-2)-7 | | x-1(4x-7)=5x-(x+21) | | 3(x-9)=-39-x | | 7x+3=-7.5 | | (-A-5B+2)5AB= | | -4+6x=-34 | | 0.3(r+2)=-1.0(-2r-4) | | 6t^2+2t=2t(3t+1) | | 2y+3=3(0)-7 | | -7(p-8)= | | -2v-14=8(v+2) | | 4t=38+2t | | n-8=22+4 | | 3(4+4n)=18n+12-6n | | -5(x+7)= | | (2x+4)x=240 | | 6/15=3/x | | 2n^2=90 | | x(6)=60 | | n+3=17+4 | | 9h+11=5h-17 | | 2x(2x)= | | x(13)=52 | | 8x+9y=818 | | 400-313=x | | 6(b+4)=0 |